2021
DOI: 10.1130/g49550.1
|View full text |Cite
|
Sign up to set email alerts
|

Monthly insolation linked to the time-transgressive nature of the Holocene East Asian monsoon precipitation maximum

Abstract: More than 10% of the world’s population lives in the East Asian monsoon (EAM) region, where precipitation patterns are critical to agricultural and industrial activities. However, the dominant forcing mechanisms driving spatiotemporal changes in the EAM remain unclear. We selected Holocene records tracking monsoon precipitation in the EAM region reconstructed from pollen data to explore the spatiotemporal patterns of monsoon precipitation changes. Our analysis shows a time-transgressive pattern of maximum prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Cai et al 2021, Zhang et al 2021c. Modern observations showed a northward migration of the EASM rain belt from late May to early August (Xiao et al 2018), in response to a northward movement of the WPSH (Zhou et al 2022). The position and intensity of the WPSH were closely related to sea surface temperature (SST) in the Tropical Pacific.…”
Section: Possible Forcing Mechanisms Of the Anti-phase Relationshipmentioning
confidence: 99%
See 4 more Smart Citations
“…Cai et al 2021, Zhang et al 2021c. Modern observations showed a northward migration of the EASM rain belt from late May to early August (Xiao et al 2018), in response to a northward movement of the WPSH (Zhou et al 2022). The position and intensity of the WPSH were closely related to sea surface temperature (SST) in the Tropical Pacific.…”
Section: Possible Forcing Mechanisms Of the Anti-phase Relationshipmentioning
confidence: 99%
“…In the EASM region, relatively low/high tree pollen percentages in Hulun Lake (Figs 1a and 6g) (Zhang, Xiao and Xu, 2022b), low/high mean annual precipitation (MAP) reconstructed from pollen assemblages in Moon Lake (Figs 1a and 6h) (Zhou et al 2022), Daihai Lake (Figs 1a and S4k) (Xiao et al 2004, Xu et al 2010 and Gonghai Lake (Figs 1a and 6i) (Chen et al 2015a), low/high values of the summer monsoon index (SMI) inferred from Qinghai Lake (Figs 1a and S4m) (An et al 2012), high/low values of anhysteretic remanent magnetization/saturation isothermal remanent magnetization (ARM/SIRM) ratio of a stalagmite from Heshang Cave (indicating decreasing/increasing transport of coarse magnetic particles associated with weak/ heavy rainfall) (Figs 1a and 6j) (Xie et al 2013), and low/high TOC contents (indicating low/high water levels) in Emerald Peak (EP) Lake (Figs 1a and S4o) (Selvaraj et al 2012) indicated a generally weak/strong EASM intensity from 3500 to 2300/2300 to 1000 cal a BP. The MWP/LIA was generally characterized by a strong/weak EASM intensity (Figs 6i,j and S4o), which was also supported by a large amount of paleoclimatic evidence from the northeastern Tibetan Plateau (e.g.…”
Section: Comparison With Paleoclimatic Records In the Easm Regionmentioning
confidence: 99%
See 3 more Smart Citations